Degradation of cattle dung by dung beetles in tropical grassland in Veracruz, Mexico - CRUZ R., MAGDALENA; MARTÍNEZ M., IMELDA; LÓPEZ-COLLADO, JOSÉ; VARGAS-MENDOZA, MÓNICA; GONZÁLEZ-HERNÁNDEZ, HÉCTOR; PLATAS-ROSADO, DIEGO E. (Revista Colombiana de Entomología, 2012)
The involvement of dung beetles on the dung degradation in a tropical pasture during the rainy and dry seasons was studied. The dung weight loss was evaluated with two treatments: dung covered with mesh (BT) and uncovered dung (BD). Thirty 2-kg dung pats were randomly placed on pasture in BT-BD pairs. Observations of the status and dung weight were made at each season at 4, 8, 16, 32, and 64 days, and the abundance and diversity of dung beetles were recorded. Euoniticellus intermedius, Digitonthophagus gazella and Copris lugubris were abundant in the first week in BD. The effect of treatment and time on the weight of dung was analyzed with a multiple linear regression model. The model allowed to calculated differences of weight loss between treatments and between times, and to determinate the time needed to have 80% of weight lost. Dung pats lost weight at a greater rate for the BD as compared to the BT treatment in both seasons. The weight loss of BT and BD both were higher and faster in the rainy season; in one month BD lost weight 92% and 67% for the BT units. In one month of the dry season BD lost 73% of their weight, while BT units lost 58%. In the rainy season 80% of dung weight loss was reached in 3 days for BD, and the same loss in 17 days for BT. In the dry season 80% of the dung weight was lost in 17 and 56 days for BD and BT respectively.